2021
DOI: 10.3390/biology10121322
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness and Perceptions of Invasive Alien Species in Small Towns

Abstract: Invasive alien species (IAS) are a growing threat globally and cause a variety of ecological, economic, and social impacts. People can introduce IAS and facilitate their spread, and can also implement, support, or oppose their management. Understanding local knowledge, awareness, and perceptions are therefore crucial if management and policy are to be effective. We administered questionnaires to members of the public in eight small towns along the Berg River Catchment in the biodiverse fynbos biome of South Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In our study, all stakeholder groups demonstrated a high level of interest in the topic of invasive species. This clearly distinguishes the stakeholder groups from the general population, where a previous study found that a good third were not interested in invasive species at all (Jubase et al 2021). Only administrative employees in the regulatory authority showed slightly less interest, but this can be explained by the regulatory authority's focus.…”
Section: Interest and Perception Of Invasive Speciesmentioning
confidence: 80%
See 2 more Smart Citations
“…In our study, all stakeholder groups demonstrated a high level of interest in the topic of invasive species. This clearly distinguishes the stakeholder groups from the general population, where a previous study found that a good third were not interested in invasive species at all (Jubase et al 2021). Only administrative employees in the regulatory authority showed slightly less interest, but this can be explained by the regulatory authority's focus.…”
Section: Interest and Perception Of Invasive Speciesmentioning
confidence: 80%
“…This result is also consistent with a previous study, which also found the damage done by invasive species is often underestimated (Waliczek et al 2017). One possible explanation for this could be that invasive species are not only associated with economic or environmental problems, but also perceived positively in the population, especially if they are attractive or bring value in the form of ecosystem services (Dickie et al 2014;Jubase et al 2021). In addition, the economic damage caused by invasive species is not always directly visible.…”
Section: Number Of Invasive Species and Economic Damagementioning
confidence: 99%
See 1 more Smart Citation
“…To address the challenge of disrupted nutrient cycling, management strategies should aim to control invasive plant species and restore native plant communities (Cao et al, 2011;Kostina-Bednarz et al, 2023). South Africa for instance is a country which took early measures to protect its native ecosystems (Jubase et al, 2021). Managed removal of invasive species can help alleviate the allelopathic pressure on native plants and promote the recovery of nutrient cycling processes (Alldred et al, 2016).…”
Section: Disrupted Nutrient Cycling and Their Availabilitymentioning
confidence: 99%